The effect of vacuum pressure on the flammability limits of H2 enrichment in natural gas (NG) - Azza Nurain, Kairallah (2010)
Hydrogen- enriched natural gas has been widely used in all over the world for application in gas turbine and internal combustion engine. The theory behind this concept is the addition of hydrogen in natural gas can extend the lean operation limit, improve the lean burn ability, and decrease the emission of NOx, CO and unburned hydrocarbon. The aims of this study are to determine the effect of vacuum pressures on the flammability limits of hydrogen enrichment in natural gas. In this experiment, methane is use to replace the natural gas. The experiments were performed in a 20 L closed explosion vessel. The mixtures were ignited by using spark permanent wire that placed at the centre of the vessel. The explosion pressure data is used to determine the flammability limits, when the low pressure is used in the explosion, the explosion limit will become wide. In this study, the result shows the flammability limits of methane is from 5 % volume to 15 % volume of methane and have revealed that the addition of hydrogen in methane /air mixture will reduce the lower flammability limit initially at 5 % volume to 1 % volume of methane at 0.98 bar. As the conclusion, we can come out that explosion of methane at lower pressure with addition of hydrogen has proven benefit of widen the flammability limit of methane, improving the combustion stability, reduce the emission of NOx, CO and unburned hydrocarbon and decreasing the spark timing. Hence, the cold start phenomenon that usually occurs at the initial stage of combustion could be overcome by adding hydrogen at low pressure.